Current Status and Future Direction of Physician-Scientists Training in Korea - Won Ji Song; Si-Hyung Lee; Jin Ho Chung (Elsevier, 2022)
In their new JID Innovations article, "Training Physician-Scientists for Careers in Investigative Dermatology," Li et al. (2022) describe the difficulties of nurturing physician-scientists in the United States and their causes. In Korea, the importance of physician-scientists is also being emphasized, and medical schools and the government are making great efforts to foster physician-scientists as well. As a result of these efforts, the number of those obtaining a doctoral degree after residency training in clinical departments, including dermatology, is increasing in Korea. However, more systematic support from the government, medical schools, and their affiliated hospitals is needed so that more physician-scientists can conduct research to identify the causes of diseases and develop new treatments while practicing medicine. In this commentary, we would like to comment on the situation of physician-scientists in Korea.